Managing Azathioprine-Induced Myelosuppression and Alopecia Totalis: Lessons from a SLE Patient - Saumya Dinithi Rupasinghe; Duminda Abeysinghe (Journal of Clinical Rheumatology and Immunology)
Introduction Azathioprine (AZA), an immunosuppressant and mercaptopurine analog, is used to manage rheumatological and immunological conditions. Although effective, AZA can cause myelosuppression, sometimes necessitating dose adjustments or discontinuation. While severe pancytopenia or alopecia is rare, these issues can arise. This report describes a case of severe myelosuppression and alopecia totalis following AZA treatment in a patient with systemic lupus erythematosus (SLE). Case Report A 27-year-old healthy female presented with an 8-month history of fever, cough with pleuritic chest pain, and hemoptysis. Clinical and biochemical evaluations diagnosed her with SLE and secondary pulmonary vasculitis. She was initially treated with systemic steroids, followed by AZA. AZA was started at 25 mg daily (0.8 mg/kg) and increased to 75 mg daily (2 mg/kg) over three months. After dose escalation, she developed increased hair loss, feverishness, and lethargy, prompting her admission to a medical facility. Examination revealed significant non-scarring alopecia, (Figure 1) but no clinical signs of an SLE flare. Laboratory tests showed pancytopenia: hemoglobin 8.4 g/dL, white blood cells 880/[Formula: see text]L, platelets 130K/[Formula: see text]L, and absolute neutrophil count 38/[Formula: see text]L. Inflammatory markers, complement levels, and septic screening were normal. AZA was discontinued, and she was treated for neutropenic sepsis with high-dose steroids and GM-CSF. Despite these measures, blood parameters did not improve as expected. After 25 days of treatment, hair loss ceased, and cytopenias began to recover. Bone marrow analysis was not performed during the acute phase. Upon discharge, her blood counts were WBC 6,130/[Formula: see text]L, hemoglobin 10.9 g/dL, and platelets 85K/[Formula: see text]L. Given her SLE and lung pathology, she continued immunosuppressive therapy but was switched from AZA to IV Rituximab. Six weeks later, her blood counts had improved (WBC 10K/[Formula: see text]L, hemoglobin 10.9 g/dL, platelets 289K/[Formula: see text]L), and hair regrowth was observed. (Figure 2) Conclusion This case underscores the need for clinicians to be vigilant for early signs of severe myelosuppression, such as alopecia, in patients receiving azathioprine. Awareness of these uncommon side effects is crucial for effective management.